A Rare Case of Inflammatory Pseudotumor with Both Involvement of Lung and Heart - SÜNBÜL, MURAT; BİRKAN, YAŞAR (GEORG THIEME VERLAG KG, 2013)
Inflammatory pseudotumor (IPT) is a rare disorder that is benign and tumor-like reactive masses with unknown etiology. The mass usually confines to the lung but other organs involvement such as liver, stomach, lymph nodes could affect. IPT of heart is usually determined with children and young adults. Only 15 cases are detected in adults. We present here a rare case of IPT with both involvement of lung and heart.
Keywords: inflammatory pseudotumor; cardiac neoplasms; mediastinal tumor; TUMOR